Application of casein-coated dual-targeting magnetic iron oxide in preparation of contraceptive drugs

Through casein-encapsulated dual-targeted magnetic iron oxide nanoparticles, anti-lutein receptor coupling and casein layer modification, the problems of low heating efficiency and oral drug stability of thermal contraception are solved, and efficient male contraception is achieved Effect.

CN119185248APending Publication Date: 2024-12-27NANTONG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311592616.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing male contraception methods are limited, especially thermal contraception methods are inefficient in heating efficiency and lack of targeting, and the degradation and stability of oral nanomedicines in the gastrointestinal tract lead to low bioavailability.

Method used

The dual-targeted magnetic iron oxide nanoparticles wrapped in casein are used to improve the stability of nanoparticles in the gastrointestinal tract and testicular targeting through anti-lutein receptor coupling and casein layer modification, and achieve the alternating magnetic field. Magnetothermal therapy.

Benefits of technology

The enrichment content and heating efficiency of nanoparticles in the testicles were significantly improved, and the reversible male contraception effect was achieved, and stability and low toxicity were maintained in the gastrointestinal tract.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119185248A_ABST
    Figure CN119185248A_ABST
Patent Text Reader

Abstract

The invention discloses an application of casein-coated dual-targeting magnetic iron oxide in preparation of contraceptive drugs, which is characterized in that core Fe3O4 nanoparticles are coupled with an anti-luteinizing hormone receptor (Anti-LHR), and then are coated with a casein layer. The casein-coated dual-targeting magnetic iron oxide shows remarkable stability in a stomach environment, and after the casein-coated dual-targeting magnetic iron oxide reaches intestinal tracts, casein on the surface is subjected to enzymatic lysis, so that Anti-LHR is exposed; the enrichment content of IONPs in testis can be effectively increased by oral administration of the magnetic iron oxide, and sufficient heat is generated under an alternating magnetic field, so that male reversible contraception is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedicine, and specifically relates to the application of casein-wrapped dual-target magnetic iron oxide in the preparation of male contraceptive drugs. Background Art

[0002] Contraception has always been an important reproductive issue. Currently, the most commonly used contraceptive methods for men are only condoms and vasectomy. Despite great efforts in the past few years, researchers have not been able to provide men with new male contraceptive options. Male spermatogenesis is temperature-dependent, and slight testicular hyperthermia can temporarily inhibit spermatogenesis, leading to infertility. Thermal contraception can restore spermatogenesis and preserve fertility, and overcome the limitations of vasectomy-based contraceptive methods, such as surgical risks of vasectomy and the fact that reversal surgery is always unsuccessful. Hot water baths were the first method to systematically study thermal contraception. However, its low heating efficiency and non-targeted nature hinder the widespread application of thermal contraception.

[0003] With the rapid development of nanotechnology, the unique properties of various nanomedia have provided new avenues for the application of nanotechnology. The inventors previously used photothermal therapy (PTT) of gold nanorods (Au NRs) to achieve male controllable contraception through in situ testicular injection, which provided inspiration for the development of new male contraceptive methods. However, the severe pain during injection, the damage of light to the skin, and the chronic toxicity caused by the non-degradability of Au NRs have limited its further clinical research. Magnetic iron oxide nanoparticles (IONPs) have many unique advantages, such as good biocompatibility and biodegradability, and most interestingly, significant magnetization and superparamagnetism, and have been approved by the FDA for tumor hyperthermia. Compared with PTT, microwave heat and ultrasonic heat, IONPs-induced magnetic hyperthermia has more advantages due to its non-invasiveness and magnetic targeting. The inventors' previous studies found that IONPs can be enriched in the interstitial tissue of the mouse testis after tail vein injection and under magnetic field navigation, and then the application of an alternating magnetic field (AMF) can achieve reversible contraception by targeted heating of the testis.

[0004] Despite the promise, male contraception based on IONPs still faces two major challenges. First, in vivo studies have shown that insufficient IONPs content in the testis may be due to poor single-targeting ability, resulting in low heating efficiency. Recent advances in surface chemistry have shown that modifying the surface of NPs with suitable targeting ligands related to receptors present on the target cell membrane can promote the absorption of NPs. Luteinizing hormone receptor (LHR) is a glycoprotein specifically expressed on the surface of male Leydig cells. Some reports have confirmed that the targeting efficiency to Leydig cells can be improved by coupling targeting molecules with LHR antibodies (Anti-LHR). However, ligand-modified NPs often show low diffusion capacity and poor stability after oral administration. Second, intravenous injection often brings inconvenience and discomfort, while oral administration avoids these defects and is therefore the first choice. However, the strong acidity and digestive enzymes in the gastrointestinal tract will degrade oral administration, resulting in low bioavailability.

[0005] In order to improve the bioavailability of oral drug formulations, an important strategy is to build a protective surface layer that can protect the drug from premature degradation and control the release of the drug. Casein is a natural protein that can form micellar porous structures. It exhibits high amphiphilicity, good dispersibility and rapid reconstitution under physiological conditions. Therefore, it is feasible to use casein as a protective layer for oral drugs. However, the functionalization of the material surface should be combined with strong targeting, high stability, controlled release and low toxicity, which will make the construction of nanomaterials more challenging. Summary of the invention

[0006] The present invention aims to provide a casein-coated dual-targeted iron oxide nanoparticles (IONPs), wherein the core Fe3O4 nanoparticles are coupled with anti-luteinizing hormone receptor (Anti-LHR) and then coated with a casein layer.

[0007] The nanoparticles are prepared by the following steps:

[0008] Step 1, preparation of citrate-stabilized Fe3O4 nanoparticles, dissolving 6.48 g FeCl3·6H2O and 1.2 g trisodium citrate in 120 mL ethylene glycol, then adding 1.20 g NaAc, stirring and mixing, sealing the mixture in an autoclave for reaction, cooling to room temperature, removing ethylene glycol, washing the black product with ethanol and deionized water to obtain iron oxide nanoparticles CA@Fe3O4 NPs;

[0009] The stirring and mixing conditions were 1000 rpm for 30 minutes;

[0010] The reaction conditions are 100-200°C for 5-10 hours, preferably 200°C for 8 hours;

[0011] Step 2, preparation of CA@Fe3O4-Anti LHR, resuspend the prepared CA@Fe3O4 NPs in 25 mL of deionized water, add 25 mL of 0.2 M MES containing 50.0 mg NHS and 50.0 mg EDC, stir and add 5.0 mg NH2-PEG-NH2 for reaction, wash the product with deionized water and dry the water, then disperse it in 50.0 mL of 0.1 M MES, then add 1.0 mL of 0.1 M MES containing 1.0 mg NHS, 1.0 mg EDC and 5.0 μL 1.0 mg / mL Anti-LHR, stir overnight at 4 ° C, collect the product by magnetic separation, wash and dry to obtain antibody-coupled nanoparticles CA@Fe3O4-Anti LHR;

[0012] Step 3, preparation of CA@Fe3O4-Anti LHR-CN, CA@Fe3O4-Anti LHR was dispersed in 50 mL of deionized water, 120 mg of casein was treated with 300 μL of 1.0 M NaOH solution and then added to the CA@Fe3O4-Anti LHR dispersed solution, the mixture was left at room temperature for 24 hours, and then 72.0 μL of freshly prepared 0.4% glutaraldehyde solution was dropped into the above mixed solution to carry out a cross-linking reaction, washed with water, collected by magnetic separation, and then dispersed in water to obtain CA@Fe3O4-Anti LHR-CN.

[0013] The second purpose of the present invention is to provide the use of the above-mentioned iron oxide nanoparticles in the preparation of male contraceptive drugs.

[0014] Furthermore, the application is to use the above iron oxide nanoparticles as the only active ingredient in combination with an alternating magnetic field and a permanent magnet.

[0015] like Figure 1As shown, the present invention designs casein-coated dual-targeted iron oxide nanoparticles (IONPs) as oral thermal agents for male thermal contraception. Among them, the core Fe3O4 nanoparticles are coupled to the anti-luteinizing hormone receptor (Anti-LHR) and then wrapped with a casein layer. After oral administration, IONPs show remarkable stability in the gastric environment, and the highly magnetized and superparamagnetic Fe3O4 core realizes magnetic targeting and magnetic hyperthermia. After reaching the intestine, the surface casein is enzymatically cleaved to expose the Anti-LHR, and the cellular uptake of interstitial cells is enhanced by active targeting. In vivo studies have confirmed that oral administration of this dual-targeted material can effectively increase the enrichment content of IONPs in the testis and generate sufficient heat under an alternating magnetic field to achieve reversible contraception. These results collectively indicate that this method has great application potential in male contraception.

[0016] The nanoparticles of the present invention have the following effects:

[0017] (1) Casein encapsulation can be used as an oral thermal agent: After iron oxide is encapsulated with casein, dual-targeted IONPs show significant stability in the gastric environment. After reaching the intestine, the surface casein is enzymatically cleaved, thereby exposing the Anti-LHR.

[0018] (2) Dual targeting of active targeting and magnetic targeting improves testicular targeting: Active targeting and magnetic navigation dual targeting enhance the cellular uptake of interstitial cells. In vivo studies have confirmed that oral administration of this dual targeting material can effectively increase the enrichment of IONPs in the testis and generate sufficient heat under an alternating magnetic field to achieve reversible contraception. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a schematic diagram of the dual-targeted casein-coated iron oxide nanoparticles of the present invention used as an oral thermal agent for male contraception.

[0020] Figure 2 Characterization of CA@Fe3O4 NPs and CA@Fe3O4-Anti LHR-CN. (A) is the SEM and TEM images of CA@Fe3O4 NPs; (B) is the Alexa CLSM image of CA@Fe3O4-Anti LHR treated with 555; (C) SEM and TEM images of CA@Fe3O4-Anti LHR-CN; (D) XRD spectrum; (E) TGA curve; (F) hysteresis loop and magnetic attraction response of AMF (403kHz) at different output currents; (G) and (H) are the temperature change curves of CA@Fe3O4 and CA@Fe3O4-Anti LHR-CN at different concentrations, respectively.

[0021] Figure 3 In the figure, (A) is the SEM of CA@Fe3O4 and CA@Fe3O4-Anti LHR-CN treated with SGF and SIF, scale bar = 50 nm; (B) is the SDS-PAGE analysis of CA@Fe3O4-Anti LHR-CN (I) and treated with SGF (II) and SIF (III), respectively; (C) is the SDS-PAGE analysis of CA@Fe3O4-Anti LHR-CN treated with SIF, and the Alexa Fluor Spectroscopy results are shown in Figure 5. CLSM images of 555 incubation.

[0022] Figure 4 Middle: The left picture shows the Prussian blue-stained microscope images of TM-3, C18-4, and GC-1 cells after incubation with CA@Fe3O4 and CA@Fe3O4-Anti LHR; the right picture shows the ICP-MS analysis of iron uptake by different cells.

[0023] Figure 5 In the figure, (A) is a schematic diagram of the mouse model of oral thermal contraception; (B) is a thermal infrared image of the mouse testicles after different treatments recorded at different time points; (C) is the curve of testicular temperature change over time of mice in the experimental group; (D) is a cross-section of the testicles stained with Prussian blue.

[0024] Figure 6 In the figure, (A) is the testicle photographs of each group at 7, 30, and 60 days after treatment (scale bar = 5.0 mm); (B) and (C) are H&E-stained testicular and epididymal sections of mice at 7, 30, and 60 days, respectively (scale bar = 50 μm); (D) and (E) are the fertility index and the average number of pups / pregnant mothers (N = 5) of male mice at 7 and 60 days after treatment, respectively, and NU means none. DETAILED DESCRIPTION

[0025] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.

[0026] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0027] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0028] Example 1

[0029] Preparation of IONPs

[0030] (1) Preparation of CA@Fe3O4 NPs

[0031] First, FeCl3·6H2O (6.48 g, 24.0 mmol) and trisodium citrate (1.2 g, 4.08 mmol) were dissolved in ethylene glycol (120 mL). Then NaAc (1.20 g) was added and stirred at 1000 rpm for 30 minutes. After that, the above mixture was sealed in a stainless steel autoclave (25 mL×8), reacted at 200°C for 8 hours, and then cooled to room temperature. Ethylene glycol was removed, and the black product was washed with ethanol and deionized water, dried and set aside.

[0032] (2) Preparation of CA@Fe3O4-Anti LHR

[0033] The prepared CA@Fe3O4 NPs were resuspended in deionized water (25 mL), and a MES solution (0.2 M, 25 mL) containing NHS (50.0 mg) and EDC (50.0 mg) was added and stirred for 20 min, then connected with NH2-PEG-NH2 (5.0 mg, Mw = 2000) and the reaction was continued for 2 h. Then, it was washed three times with deionized water and the water was dried. Then, Anti-LHR (5.0 uL, 1.0 mg / mL, abcam, ab204950) containing NHS (1.0 mg) and EDC (1.0 mg) dissolved in MES (1.0 mL, 0.1 M) was added to the above suspension (dispersed in 50.0 mL MES, 0.1 M) and stirred overnight at 4 ° C. Then, the product was collected by magnetic separation, followed by washing and drying.

[0034] (3) Preparation of CA@Fe3O4-Anti LHR-CN

[0035] The CA@Fe3O4-Anti LHR obtained above was dispersed in deionized water (50mL) and turned into a brown solution. Casein (120mg) was pretreated with NaOH solution (1.0M, 300μL) to form a soluble base. The treated casein was then added to the CA@Fe3O4-Anti LHR solution. The mixture was left at room temperature for 24 hours to allow the casein molecules to aggregate on the surface. A freshly prepared 0.4% glutaraldehyde solution (72.0μL) was dropped into the above mixed solution. After the cross-linking reaction was carried out for 2h, it was washed with water, collected by magnetic separation, and then dispersed in water. The resulting CA@Fe3O4-Anti LHR-CN stock solution was stored at 4℃ for future use.

[0036] The prepared CA@Fe3O4 NPs, CA@Fe3O4-Anti LHR and CA@Fe3O4-Anti LHR-CN (IONPs) were tested as follows:

[0037] 1. In vitro magnetic targeting evaluation

[0038] A permanent magnet was placed near a quartz cuvette containing 3.0 mL CA@Fe3O4 and CA@Fe3O4-Anti LHR-CN (10 mg / mL, in terms of iron atoms) to evaluate the magnetic targeting ability of IONPs, and photos were taken after 3 min of magnetic attraction.

[0039] 2. Evaluation of extracorporeal magnetic hyperthermia

[0040] The IONPs solution was diluted with PBS to different concentrations and placed in a centrifuge tube (1.5 mL). The centrifuge tube was placed in the center of a 403 kHz electromagnetic induction heating coil. PBS was used as a blank control. The temperature was monitored and recorded by an infrared thermal imager (FLIR E5).

[0041] 3. Stability of IONPs in the gastrointestinal environment

[0042] Simulated gastric fluid (SGF) and simulated intestinal fluid (SIF) were prepared as previously reported (Biomaterials, 2019, 197, 86-100). SGF: 0.2 g NaCl, 7.0 mL HCl (1.0 N) and 0.5 g pepsin were added to deionized water to a total volume of 50 mL (pH 1.2); SIF: 6.8 g KH2PO4, 0.896 g NaOH and 0.5 g trypsin were added to deionized water to a total volume of 50 mL (pH 6.8). The freshly prepared IONPs were dispersed in SGF (with or without pepsin) and SIF, respectively, and then incubated at 37 °C in a shaker for 24 h. The particle morphology and particle size were measured by scanning electron microscopy (SEM) and particle size analyzer (DLS).

[0043] 4. In vitro cellular uptake and targeting of IONPs

[0044] TM-3, C18-4, and GC-1 cells were seeded in 24-well slides at a concentration of 80,000 cells per well. After 24 hours of recovery, the culture medium containing CA@Fe3O4 (500μL, 0.1μg / mL, Fe) and CA@Fe3O4-Anti LHR (500μL, 0.1μg / mL, Fe) was replaced and the cells were incubated at 37°C for 4 hours. Then, the cells were rinsed with PBS and fixed with 4% paraformaldehyde (PFA). Finally, Prussian blue staining of iron was performed to explore cell targeting, and then observed under an optical microscope.

[0045] 5. Study on in vivo magnetic hyperthermia after oral administration

[0046] Male mice were orally administered IONPs containing 1.0 g Fe / kg (body weight) or PBS once a day for different days. Immediately after each administration, a permanent magnet was placed next to the testicles for 4 hours for magnetic targeting. Subsequently, a 403kHz alternating magnetic field with an output current of 30A was applied to the mouse testicles for 20 minutes. During the treatment period, the infrared thermal imager captured thermal images every 60 seconds. The treated mice continued to be fed and observed, and were killed on the 7th, 30th, and 60th days. The heart, liver, spleen, lungs, kidneys, testicles, and epididymis were collected at each time point and stored in a -80°C refrigerator for subsequent studies.

[0047] 6. Fertility determination

[0048] The fertility index of male mice was measured on days 7 and 60 after treatment. Each male mouse was cohabitated with two untreated female mice for 7 days, and the female mice were separated from the male mice after mating. Pregnant mice were observed every two days to determine the time of delivery. The number of pups was recorded after birth.

[0049] The test results are as follows:

[0050] (1) Construction of dual-targeting IONPs

[0051] In order for IONPs to have the functions of magnetic navigation and magnetic hyperthermia, IONPs must have both high magnetization and superparamagnetism. However, these two contradictory properties are usually difficult to exist simultaneously in traditional iron oxide nanomaterials. IONPs with a particle size of 10 nanometers have superparamagnetism, but generally exhibit lower magnetization intensity. Increasing the particle size can increase the magnetization intensity, but it will reduce the magnetothermal conversion ability. To solve this problem, the inventors designed an improved solvothermal method to prepare citrate-stabilized Fe3O4 nanoparticles (CA@Fe3O4 NPs). The scanning electron microscope (SEM) image shows ( Figure 2 (A) The average particle size of CA@Fe3O4NPs is about 60nm. High-resolution transmission electron microscopy (HR-TEM) shows that the nanoparticles are composed of many small particle units with a size of 5-10 nanometers. In this structure, the magnetic moment of a single particle increases sharply with the increase of particle size while maintaining superparamagnetism.

[0052] After obtaining the desired magnetic Fe3O4 core, the inventors then modified it layer by layer. First, CA@Fe3O4 NPs were coupled with Anti-LHR to form CA@Fe3O4-Anti LHR. After incubating the fluorescent secondary antibody with CA@Fe3O4-Anti LHR, the red fluorescence signal under the confocal laser scanning microscope (CLSM) confirmed the successful coupling ( Figure 2Next, CA@Fe3O4-Anti LHR was coated with casein (CA@Fe3O4-Anti LHR-CN) to overcome the gastrointestinal barrier during oral delivery. As expected, CA@Fe3O4-Anti LHR-CN exhibited a relatively uniform morphology, while the size of the CA@Fe3O4 core remained unchanged ( Figure 2 C). Under transmission electron microscopy, after negative staining, a protein coating with a thickness of about 8 nm was observed around the CA@Fe3O4 core (see Figure 2 C). At the same time, due to the presence of negatively charged carboxyl groups in casein, the hydrodynamic size increased from 70 nm to 95 nm, and the surface negative charge increased significantly from -21.6 ± 2.3 mV to -43.1 ± 1.6 mV, further proving the presence of the casein coating. In addition, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) bands confirmed the successful encapsulation of casein on CA@Fe3O4-Anti LHR-CN. In addition, the Fourier transform infrared (FT-IR) of CA@Fe3O4-Anti LHR-CN showed that the 1630 and 1530 cm -1 The absorption band at 1242 cm corresponds to the stretching vibration of C=O and CN. -1 The absorption bands at correspond to CN stretching and NH deformation vibrations, which are associated with the amide bands of proteins, further indicating the presence of casein. It is noteworthy that CA@Fe3O4-Anti LHR-CN exhibits better colloidal stability compared to CA@Fe3O4 NPs, indicating that casein plays a crucial role in the stabilizing effect.

[0053] To apply them in vivo, the inventors systematically characterized the physicochemical properties of the constructed IONPs. Figure 2 D is the X-ray diffraction (XRD) pattern of CA@Fe3O4 NPs and CA@Fe3O4-Anti LHR-CN, indicating that the formed structure is an inverse spinel single-phase Fe3O4 (JCPDS NO.19-0629). These strong and sharp peaks confirm that the formed nanoparticles are highly crystalline. Thermogravimetric analysis (TGA) shows that in the range of 100-1000℃, CA@Fe3O4 and CA@Fe3O4-Anti LHR-CN lose about 16.24wt% and 16.55wt% respectively ( Figure 2 (E). The greater mass loss in CA@Fe3O4-Anti LHR-CN may be related to the removal of additional organic substances (such as antibodies and casein) from the surface. After determining the structure of IONPs, the inventors tested their magnetic and magnetocaloric properties. From the magnetization curve ( Figure 2F) shows that both exhibit superparamagnetism, with a saturation magnetization of 60.57emu / g for CA@Fe3O4 and 55.68emu / g for CA@Fe3O4-Anti LHR-CN (zero remanence and coercivity), which allows them to be quickly collected by commercial magnets. Next, the in vitro magnetocaloric properties of the IONPs suspension were tested at 403kHz AMF, and the temperature was detected using an infrared thermal imager. Figure 2 As shown in G and H, the temperature of CA@Fe3O4 and CA@Fe3O4-Anti LHR-CN suspensions increased significantly over time and eventually remained constant; PBS had no thermal response to AMF. Although the magnetothermal conversion efficiency of CA@Fe3O4-Anti LHR-CN was slightly lower than that of CA@Fe3O4, it could still reach 88.1℃ by adjusting the nanoparticle concentration and AMF output current, indicating its potential application in male thermal contraception.

[0054] (2) Stability test results of IONPs in the gastrointestinal environment

[0055] Oral administration of IONPs needs to overcome the gastric acid and enzymatic conditions of the gastrointestinal tract. With this in mind, the inventors first tested the stability of IONPs in a severely acidic gastric environment (pH 1.2). Figure 3 As shown in Figure 1, the exposed CA@Fe3O4 NPs were severely corroded as observed by SEM, which was further confirmed by the significant increase in the hydrodynamic size measured by DLS due to precipitation. In contrast, the material morphology and hydrodynamic size of CA@Fe3O4-Anti LHR-CN remained basically unchanged over a period of time at pH 1.2, indicating that the presence of casein protected them from degradation in a strong acidic environment and the structure was well preserved.

[0056] In order to investigate the enzymatic degradation of the outer casein in the stomach and intestine, the inventors treated CA@Fe3O4-Anti LHR-CN with pepsin (simulated gastric fluid, SGF) at pH 1.2 and trypsin (simulated intestinal fluid, SIF) at pH 6.8. SEM showed that it had high dispersibility in SGF, and the morphology and particle size did not change ( Figure 3 A), and DLS test confirmed this. From the results of SDS-PAGE, the casein bands after SGF treatment still exist ( Figure 3B), indicating that the casein layer still exists on the surface of the material; while the casein bands in SDS-PAGE disappeared after SIF treatment. At the same time, surface protein degradation was observed by SEM, and the reduction in hydrodynamic size obtained by DLS further confirmed the decomposition of casein. After the outer casein was enzymatically hydrolyzed, the internal CA@Fe3O4-Anti LHR was exposed to SIF. In order to test the effect of SIF on the surface Anti LHR, the applicant further incubated it with a fluorescent secondary antibody, and the red fluorescence in CLSM indicated that Anti LHR was not degraded by the digestive fluid ( Figure 3 C). It is noteworthy that CA@Fe3O4-Anti LHR-CN can maintain normal magnetic properties after being treated with SGF and SIF, as evidenced by its attraction to magnets. The above results indicate that CA@Fe3O4-Anti LHR-CN can remain stable in the gastric tract in the presence of casein, while the external casein is degraded in the intestine, thereby exposing the internal CA@Fe3O4-Anti LHR without affecting its active targeting ability.

[0057] (3) In vitro cellular uptake and specific targeting results of IONPs

[0058] The dual targeting strategy of oral administration emphasizes that Anti-LHR enhances the selective uptake of IONPs by actively targeting Leydig cells. Therefore, the inventors evaluated its in vitro testicular targeting efficiency by comparing the cellular uptake of CA@Fe3O4-Anti LHR by TM-3 Leydig cells (overexpressing LHR) with that of CA@Fe3O4. To this end, CA@Fe3O4 and CA@Fe3O4-AntiLHR were co-incubated with TM-3 cells, respectively, followed by Prussian blue staining and ICP-MS quantitative analysis. For comparison, C18-4 and GC-1 cells expressing low levels of LHR were selected as non-targeted control cell lines. Figure 4 As can be seen in the left figure, obvious blue spots can be seen in most areas of TM-3 cells co-incubated with CA@Fe3O4-Anti LHR; while cells treated with CA@Fe3O4 have fewer blue spots. Figure 4The ICP-MS results shown in the right figure show that the iron uptake of TM-3 cells treated with CA@Fe3O4-Anti LHR is much higher than that of cells treated with CA@Fe3O4. In contrast, due to the lack of LHR on the cell membrane, the uptake of CA@Fe3O4 and CA@Fe3O4-Anti LHR by C18-4 and GC-1 cells is comparable to that of the control group. These results clearly confirm that Anti-LHR on the surface of CA@Fe3O4-AntiLHR can promote cellular uptake in TM-3 cells. It is worth noting that after incubation with CA@Fe3O4 and CA@Fe3O4-Anti LHR, the cells maintained their viability and proliferation ability without obvious morphological changes, ensuring the reliability of the cellular uptake study.

[0059] (4) In vivo magnetic thermal evaluation

[0060] On the basis of the above results, the inventors compared the in vivo magnetothermal properties after oral administration of IONPs. To this end, ICR male mice were orally administered with PBS or IONPs suspension, and a permanent magnet (MT) was placed or not in the testis, and an alternating magnetic field (AMF) of 403kHz was applied or not. After different treatment times (1 day (1D), 2 days (2D)), the testis surface temperature was monitored with an infrared thermal imager.

[0061] from Figure 5 As can be seen in Figure A, the testicular temperature of the PBS and CA@Fe3O4-Anti LHR-CN groups remained basically unchanged at around 30.0℃, while the testicular temperature of the PBS+AMF group slightly increased from 34.3℃ to 36.8℃ ( Figure 5 B and 5C). Even after the navigation magnetic field was applied to the testicles of mice that had orally taken CA@Fe3O4 NPs (CA@Fe3O4+MT-2D+AMF group), the testicular temperature only increased to 37.5°C. In contrast, the testicular temperature of the dual-targeted group increased significantly with the increase in treatment dose, reaching 40.4°C and 42.9°C in the CA@Fe3O4-Anti LHR-CN+MT-1D+AMF group and the CA@Fe3O4-Anti LHR-CN+MT-2D+AMF group, respectively. The testicular temperature of mice in the active targeting group (CA@Fe3O4-Anti LHR-CN-2D+AMF) and the magnetic targeting group (CA@Fe3O4-CN+MT-2D+AMF) only reached 39.3°C and 39.5°C, indicating that the heating efficiency of the dual-targeted treatment was higher than that of the single-targeted group. At the same time, it should be pointed out that the temperature difference in the testicular region of mice between the CA@Fe3O4-Anti LHR-CN+MT-2D+AMF group and the CA@Fe3O4-Anti-LHR+MT-2D+AMF group was more obvious at 4.6°C, indicating that surface casein played an important role.

[0062] To further confirm these results, the inventors performed Prussian blue staining to directly measure the content of IONPs in the testes. To this end, male mice received various treatments (oral administration of CA@Fe3O4, CA@Fe3O4-CN or CA@Fe3O4-AntiLHR-CN; with or without external magnets placed in the testicular area). Figure 5 As shown in D, almost no positive staining was observed in the CA@Fe3O4-2D group. In contrast, a large number of scattered blue spots were observed in the interstitial tissue of the testes of mice treated with CA@Fe3O4-Anti LHR-CN+MT-2D, while fewer blue spots were observed in mice treated with CA@Fe3O4-Anti LHR-CN-2D or CA@Fe3O4-CN+MT-2D, which highly supported the results of the in vivo magnetothermal performance study and once again confirmed the effective accumulation of IONPs by the dual-targeting strategy. Increasing evidence suggests that CA@Fe3O4-Anti LHR-CN can be feasibly applied to male contraception in both oral and dual-targeting routes.

[0063] (5) Evaluation of contraceptive effectiveness

[0064] Finally, the contraceptive effects of the two groups were compared and evaluated. According to the inventors' previous studies, 15 minutes of hyperthermia to the testicles at 43°C can achieve effective and reversible male contraception. In the present invention, the inventors evaluated the effects of CA@Fe3O4-AntiLHR-CN+MT-2D+AMF (42.9°C) on testicular function, spermatogenesis and fertility through oral administration. The mice in each group were killed 7, 30 and 60 days after treatment, and the testicles and epididymis were removed and weighed at different time points. Compared with the PBS group ( Figure 6 In the middle (A), mice treated with CA@Fe3O4-Anti LHR-CN+MT-2D+AMF showed obvious testicular degeneration on day 7, but recovered to normal size on day 60. This may be because the testicles were reversibly destroyed. It is worth noting that neither PBS+AMF treatment nor CA@Fe3O4-Anti LHR-CN treatment significantly affected the change in testicular volume, indicating that the magnetic hyperthermia method here has good biocompatibility.

[0065] Subsequently, the effect of magnetic hyperthermia on the testis was verified by histological examination. Figure 6As shown in B, the testes of mice in the CA@Fe3O4-AntiLHR-CN+MT-2D+AMF group showed degenerative changes on the 7th day, and spermatocytes and sperm cells in seminiferous tubules underwent apoptosis. Over time, the damage gradually recovered, and the testicular structure was close to normal after 60 days. In contrast, testicular tissue sections of mice treated with PBS, PBS+AMF, and CA@Fe3O4-Anti LHR-CN all showed typical testicular characteristics, including spermatogonia close to the basement membrane and sperm in the tubular lumen. According to H&E staining of the epididymal caput ( Figure 6 In Figure C), tissue sections treated with PBS+AMF and CA@Fe3O4-Anti LHR-CN showed no significant differences compared with the PBS group at any time point. However, no sperm was detected in the epididymis on day 7 after CA@Fe3O4-Anti LHR-CN+MT-2D+AMF treatment, but new sperm were observed on day 60, which is consistent with the results of CASA (computer-assisted sperm analysis). These findings are consistent with those reports that thick line spermatocytes, early spermatocytes, and mature sperm in the testis are most susceptible to heat. Therefore, short-term exposure of mouse testes to mild hyperthermia inhibits spermatogenesis, but gradually returns to normal over time.

[0066] The final exploration of contraceptive efficacy was conducted by evaluating fertility indicators ( Figure 6 D). Compared with the PBS group, the use of AMF or CA@Fe3O4-Anti LHR-CN alone did not affect fertility. The contraceptive effect of the CA@Fe3O4-Anti LHR-CN+MT-2D+AMF group was ideal, with the fertility index dropping to 0 on the 7th day after treatment and recovering to 75% on the 60th day. It is worth noting that all treatments did not affect the number of pups ( Figure 6 E), and no obvious morphological defects were observed in any of the pups. In summary, CA@Fe3O4-AntiLHR-CN+MT-2D+AMF treatment can temporarily inhibit spermatogenesis and achieve reversible contraception in males.

Claims

1. Casein-coated dual-targeted iron oxide nanoparticles, characterized in that: The preparation was carried out by the following steps: Step 1, preparation of citrate-stabilized Fe3O4 nanoparticles, dissolving 6.48 g FeCl3•6H2O and 1.2 g trisodium citrate in 120 mL ethylene glycol, then adding 1.20 g NaAc, stirring and mixing, sealing the mixture in an autoclave for reaction, cooling to room temperature, removing ethylene glycol, washing the black product with ethanol and deionized water to obtain iron oxide nanoparticles CA@Fe3O4 NPs; Step 2, preparation of CA@Fe3O4-Anti LHR, the prepared CA@Fe3O4 NPs were resuspended in 25 mL of deionized water, 25 mL of 0.2 M MES containing 50.0 mg NHS and 50.0 mg EDC was added, and 5.0 mg NH2-PEG-NH2 was added after stirring for reaction, the product was washed with deionized water and the water was dried, and then dispersed in 50.0 mL of 0.1 M MES, and then 1.0 mL of 0.1 M MES containing 1.0 mg NHS, 1.0 mg EDC and 5.0 μL 1.0 mg / mL Anti-LHR was added, stirred at 4 ° C overnight, and the product was collected by magnetic separation. After washing and drying, the antibody-coupled iron oxide nanoparticles CA@Fe3O4-Anti LHR were obtained; Step 3, preparation of CA@Fe3O4-Anti LHR-CN, CA@Fe3O4-Anti LHR was dispersed in 50 mL of deionized water, 120 mg of casein was treated with 300 μL of 1.0 M NaOH solution and then added to the CA@Fe3O4-Anti LHR dispersed solution, the mixture was left at room temperature for 24 hours, and then 72.0 μL of freshly prepared 0.4% glutaraldehyde solution was dropped into the above mixed solution to carry out a cross-linking reaction, washed with water and collected by magnetic separation, and then dispersed in water to obtain casein-coated iron oxide nanoparticles CA@Fe3O4-Anti LHR-CN.

2. The iron oxide nanoparticles according to claim 1, characterized in that In step 1, the reaction conditions are 100-200° C. for 5-10 hours.

3. Use of the iron oxide nanoparticles according to claim 1 in the preparation of male contraceptive drugs.

Citation Information

Cited By

  • Application of bismuth telluride nanosheet in preparation of male contraceptive

    CN121102469A